Corporate social responsibility, cost structures, and COVID-19: Impact of passenger behavior on business models. (December 2021) - Wild, Peter
Highlights: Differences between low-cost and network carrier airlines. Influence of corporate social responsibility on passenger's behavior. Impact of COVD-19 on the airline business models. Model's cost structures and influence on passenger's fare acceptance. Abstract: The present work is concerned with the distinction between low-cost and network carriers within the airline industry. These distinct business models follow different approaches in their external strategy and, thus, in their communication, marketing, and internal cost structure. The differences between the two models are discussed in general and in light of the ongoing trend toward more sustainable and transparent business models, thus focusing on the customer perspective. A quantitative empirical study was conducted to assess the perception of the two airline business models. Additionally, an analysis of changing flyer behavior owing to the COVID-19 crisis was conducted, and the importance of corporate social responsibility (CSR) in the airline industry was evaluated. Using a sample of self-reported frequent flyers ( n  = 99), the present study used a correlative approach to evaluate the relationship between the individual variables. Among the core findings of the study were that CSR plays an important role in the mindset of passengers, especially with respect to philanthropic and legal responsibility, and that during the COVID-19 pandemic, concerns about ecological responsibility gained momentum. Apparently, COVID-19 did not cause a demand shift within business models, and no differences in passengers' perceptions regarding CSR were detected among models. However, significant differences between low-cost and full-service airlines were found regarding their respective perceived cost structures. Passengers are aware of this difference, which implies that they might see fare differences up to 30% as reasonable.